COMPREHENSIVE FLOOD MITIGATION AND MANAGEMENT IN THE CHI RIVER BASIN, THAILAND - K. Kuntiyawichai; B. Schultz; S. Uhlenbrook; F. X. Suryadi; G. A. Corzo (Lowland Technology International, 2011)
Severe flooding of the flat downstream area of the Chi River Basin occurs frequently. This flooding is causing catastrophic loss of human lives, damage and economic loss. Effective flood management requires a broad and practical approach. Although flood disasters cannot completely be prevented, major part of potential loss of lives and damages can be reduced by comprehensive mitigation measures. In this paper, the effects of river normalisation, reservoir operation, green river (bypass), and retention have been analysed by using integrated hydrologic and hydraulic modelling. Every tributary has been simulated by a process-based hydrological model (SWAT) coupled with the 1D/2D SOBEK river routing model. Model simulation results under the design rainfall event, i.e. flood depth, flood extent, and damages for the situation with and without flood mitigation measures have been compared and evaluated to determine an optimal set of mitigation measures. The results reveal that a combination of river normalisation, reservoir operation, and green river (bypass) is most effective as it can decrease the extent of the 100-year flood event by approximately 24% and 31% for the economic damage. The results of this study will be useful for improving the present flood defence practice in the Chi River Basin.